Governance and data access mechanisms for secondary use within the European Health Data Space (EHDS) : Case ONCOVALUE on secondary use of electronic health data in value-based oncology care - Hautaniemi, Tiia (My University, 2025)
The European Health Data Space (EHDS) is the first sector-specific data space within the European Union. Together with other strategic sectoral data spaces, it will eventually form a European single market for data. The EHDS is governed by the European Health Data Space Regulation, which entered into force in March 2025. The aim of the Regulation is to establish a common framework for the use and exchange of electronic health data throughout the European Union. Within the EHDS, the secondary use of electronic health data allows access to certain health data for legally defined purposes, such as research or policymaking. This thesis examines the secondary use of electronic health data in accordance with the Regulation, with particular emphasis on its governance and mechanisms for such use. The study seeks to investigate the structures created by the EHDS for secondary use and to understand the role of EU funded projects and initiatives in the phased implementation of the Regulation. The topic is approached from the perspective of the ONCOVALUE project and its need to map the current state of affairs. The research is conducted as a contextual doctrinal study, which incorporates elements beyond traditional legal scholarship. This approach provides a multidisciplinary perspective and practical relevance to the subject under exploration by combining legal sources with materials from other fields. The study demonstrates how EU-projects and initiatives, particularly in cross-border contexts, actively participate in the implementation of the EHDS and influence the practical solutions associated with its use. Based on the findings, it can be concluded that such projects and initiatives play a central role in the successful implementation of the EHDS and in ensuring consistent governance of secondary use. Accordingly, it is essential that the development and operationalisation of the EHDS continue to involve applicable EU-projects and initiatives.

Eurooppalainen terveystietoalue, European Health Data Space (EHDS), on ensimmäinen Euroopan union yhteinen data-avaruus, joka yhdessä muiden strategisten sektoreiden data-avaruuksien kanssa tulee lopulta muodostamaan Euroopan unionin yhteisen datamarkkinan. Kyseistä terveystietoaluetta sääntelee maaliskuussa 2025 voimaantullut asetus eurooppalaisesta terveystietoalueesta, jonka tavoitteena on muodostaa yhteinen kehys sähköisten terveystietojen käytölle ja vaihdolle Euroopan Unionissa. Eurooppalaisen terveystietoalueen puitteissa tapahtuva sähköisten terveystietojen toissijainen käyttö mahdollistaa pääsyn tiettyihin terveystietoihin laissa määriteltyjen käyttötarkoitusten, kuten tutkimuksen- tai päätöksenteon, perusteella. Tässä tutkielmassa tarkastellaan asetuksenmukaista terveystietojen toissijaista käyttöä ja etenkin siihen liittyvää hallinnointia ja mekanismeja. Tarkoituksena on tutkia eurooppalaisen terveystietoalueen luomia rakenteita toissijaiseen käyttöön ja ymmärtää EU-rahoitteisten projektien ja aloitteiden merkitystä asetuksen asteittaisessa toimeenpanossa. Aihetta lähestytään ONCOVALUE -hankkeen lähtökohdista ja tarpeesta kartoittaa nykytilannetta. Tutkimus on toteutettu kontekstuaalisena lainopillisena tutkimuksena (contextual doctrinal research), jonka metodeita hyödyntäen tutkimukseen on sisällytetty perinteisen lainopin ylittäviä elementtejä. Näin tutkittavaan aiheeseen on saatu monitieteistä näkökulmaa ja tarvittavaa käytännönläheisyyttä yhdistämällä lähteitä eri aloilta. Tutkimus osoittaa, miten etenkin rajat ylittävissä tilanteissa projektit ja aloitteet ovat aktiivisesti mukana eurooppalaisen terveystietoalueen toimeenpanossa, vaikuttaen siihen, millaisia ratkaisuja sen käyttöon liittyy. Tulosten perusteella voidaan siten päätellä, että projektit ja aloitteet ovat keskeisessä asemassa yhteisen eurooppalaisen terveystietoalueen toimeenpanon onnistumisessa ja toissijaisen käytön yhdenmukaisessa hallinnassa. Tästä syystä myös jatkossa on varmistettava, että eurooppalaisen terveystietoalueen kehitykseen ja toiminnallisuuksien käyttöönottoon sisältyy tarkoituksenmukaisia EU-projekteja ja aloitteita.
Keywords: European Health Data Space, EHDS, secondary use